Analysis of the Application of Biological Agents in Obtaining Bioglycerin and Biodiesel from Recycled Edible Oils in the City of Arequipa (LACCEI, 2024)
The purpose of this study was to obtain biodiesel and bioglycerin from recycled edible oils through biological agents. By means of controlled conditions in a bioreactor designed and manufactured by the research team of the Doctoral Thesis Project. The oily medium was conditioned with respect to pH, methanol concentration and temperature according to the technical requirements of Biological Agents (Aspergillus niger, lipase from Aspergillus niger, lipase acrylic resin from Candida antarctica). In the environmental conditions of the City of Arequipa, values higher than 80% of Biodiesel and 16.5% of Bioglycerin were obtained. Biodiesel is characterized with respect to its Physicochemical Properties, by means of ASTM Methods, regarding Flash Point, Density, Phase Separation, Cetane Number, Diesel Index and Viscosity and for Bioglycerin, Infrared Spectroscopy with Fourier Transform, carried out in the Laboratory of Research and Services (LABINVSERV) of San Agustin National University Arequipa.